SIP Authentication Protocols Based On Elliptic Curve Cryptography: Survey and comparison - Mourade Azrour; Mohammed Ouanan; Yousef Farhaoui (Institute of Advanced Engineering and Science, 2016)
Session Initiation Protocol (SIP) is the most popular signaling protocol using in order to establish, modify and terminate the session multimedia between different participants. It was selected by the Third Generation Project Partnership (3GPP) as a multimedia application protocol in 3G mobile networks. SIP is the protocol currently used for signaling ToIP calls. The security of SIP is becoming more and more important. Authentication is the most important security service required by SIP. To ensure a secured communication, many SIP authentication protocols have been proposed. This work provides an overview of the proposed schemes based on elliptic curve cryptography. Those proposed schemes are analyzed in security consideration and the computational cost.